Post-postfeminism? New feminist visibilities in postfeminist times - Gill, R. (Feminist Media Studies, 2016)
This article contributes to debates about the value and utility of the notion of postfeminism for a seemingly “new” moment marked by a resurgence of interest in feminism in the media and among young women. The paper reviews current understandings of postfeminism and criticisms of the term’s failure to speak to or connect with contemporary feminism. It offers a defence of the continued importance of a critical notion of postfeminism, used as an analytical category to capture a distinctive contradictory-but-patterned sensibility intimately connected to neoliberalism. The paper raises questions about the meaning of the apparent new visibility of feminism and highlights the multiplicity of different feminisms currently circulating in mainstream media culture – which exist in tension with each other. I argue for the importance of being able to “think together” the rise of popular feminism alongside and in tandem with intensified misogyny. I further show how a postfeminist sensibility informs even those media productions that ostensibly celebrate the new feminism. Ultimately, the paper argues that claims that we have moved “beyond” postfeminism are (sadly) premature, and the notion still has much to offer feminist cultural critics.
Number: 4

Gender and creative labour - Conor, B; Gill, R; Taylor S (The Sociological Review, 2015)
Keywords: gender inequality; neoliberalism; precariousness; self-representation; sexism